Damage Localization in Composite Laminates by Building in PZT Wafer Transducers: A Comparative Study with Surface‐Bonded PZT Strategy. Issue 3 (27th December 2018) - Yang, Bin; Xuan, Fu‐Zhen; Jin, Pengcheng; Hu, Chaojie; Xiao, Biao; Li, Dan; Xiang, Yanxun; Lei, Hongshuai
Abstract : Lamb waves provide sensitive and effective approach for nondestructive inspection of large‐scale composite structures. Traditionally in Lamb wave‐based damage detection systems, the piezoelectric (PZT) wafer transducers are attached on the surface of composite components. However, surface‐bonded PZT wafers are fragile, and they may lose serviceability when external load happens. In this paper, numerical and theoretical investigations are firstly carried out to analyze the Lamb wave features generated by PZT wafers that are located in the mid‐thickness of a thin‐walled plate. Subsequently, the authors integrate the PZT wafer arrays in woven glass fiber reinforced epoxy (WGF/epoxy) laminates with stacking sequence of [90°/0°]4 . It is found that the approximate single S0 Lamb wave mode is generated by the built‐in PZT wafers. This makes the received signals very simple and easy to be interpreted. Utilizing the signals obtained by the built‐in and surface‐bonded PZT wafer transmitter‐receiver arrays, damage localization algorithms that considered the slowness profiles are compiled to help locating the defects. The compared results demonstrate that the built‐in PZT strategy has great potential for quantitative non‐destructive evaluation of composite structures. Abstract : This paper presents a built‐in PZT wafer methodology to generate S0 mode dominant Lamb wave in WGF/epoxy composites. Symmetrical dominant waves are generated by the built‐in PZT method. In both the enhanced ellipse and probabilistic imaging algorithms, the damage localization errors are limited and are kept within the range of ±10%. The built‐in PZT method has higher damage detection sensitivity.